The The Effectiveness of Interpersonal Communication in Forming Religious Character in Faith-Based Orphanage - Jarkasih, Dita Giani; Fauziah, Kholifatul (Universitas Muhammadiyah Yogyakarta, 2023)
The interpersonal skills of caregivers have an important role in shaping the religious character of the santri (student of an Islamic boarding school). Therefore, this study aims to use a descriptive qualitative research method. The process of collecting data uses interviews, observation, and documentation. The results found in this study indicate that the process of forming the religious character of students at the LKSA Panti Asuhan (Orphanage) Muhammadiyah Tuksono still needs to be optimized. In addition, the effectiveness of interpersonal communication between caregivers and santri in the characteristics of togetherness has reached an optimal level. This research produces theoretical and practical implications regarding the effectiveness of interpersonal communication in forming students’ religious character.